Peripheral Analgesic and Anti-diarrheal Activities of Leaf of Syzygium cumini (L.) Skeel (Bangladesh Pharmaceutical Journal, 2019)
Syzygium cumini has been used in folk medicine to treat many diseases. To establish the potential medicinal value of leaves of S. cumini, the current study was carried out to assess the peripheral analgesic and anti-diarrheal activities in mice model. The crude methanol extract and its petroleum ether and chloroform soluble fraction were administered to the experimental mice at a dose of 200- and 400- mg/kg b.w. (denoted as CME1, CME2, PESF1, PESF2, CLSF1 and CLSF2 respectively) using acetic acid induced writhing method and castrol oil induced anti-diarrheal assay protocol. The extract and its Kupchan fractions exhibited significant (p < 0.001) reduction of writhing response in a dose dependent manner. In the acetic acid-induced writhing test, the activity decreased in the order diclofenac (75.33%) > PESF2 (70.33%) > CME2 (67.00%) > PESF1 (64.00%) > CLSF2 (61.33%) > CME1 (56.67%) >CLSF1 (48.67%). All the fractions significantly (p < 0.001) attenuated anti-diarrheal effect in a dose dependent manner with the highest activity observed by CME2 (47.73%) as compared to standard lopeiramide (54.55%). The results of our study, being reported for the first time, provide reasonable indication that the methanol extract of S. cumini leaf and its different fractions possess peripheral analgesic and antidiarrheal activities.Bangladesh Pharmaceutical Journal 22(1): 13-17, 2019